If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5g + 9) * 7 = 0 Reorder the terms: (9 + 5g) * 7 = 0 Reorder the terms for easier multiplication: 7(9 + 5g) = 0 (9 * 7 + 5g * 7) = 0 (63 + 35g) = 0 Solving 63 + 35g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 35g = 0 + -63 Combine like terms: 63 + -63 = 0 0 + 35g = 0 + -63 35g = 0 + -63 Combine like terms: 0 + -63 = -63 35g = -63 Divide each side by '35'. g = -1.8 Simplifying g = -1.8
| -8+14= | | -2(2p-3)=3r | | 6y^2+y-15=0 | | 4s+9t-9= | | 5n-12=-3n+4 | | 4x^4+x^2-18=0 | | 9n+8=89 | | -3+8=2 | | 5a=5 | | 6x^2-9=0 | | 4(2+5)=x | | 5n-12=3n+4 | | 17-x=7 | | 5a=1 | | 5(n+2)=-17q | | -3x-9=-18 | | 2.4=.2t | | 12x+6=11-4x | | 14+3(x+8)=20 | | 4.9=.7k | | z^5-4z^3+5z=0 | | x+107=109 | | 3-2y=-7 | | 13-4r=1-x | | -2x-(-3x-8)=6 | | .33x=6-.20x | | 20=11z-2 | | 7x+17=38 | | -17-2b=b+4 | | 12x+2=40 | | 10=-3x-5 | | 13x=39 |